The Relationship Between Factors Forming Work Safety Culture And Safety Behavior At Pt Dok Dan Perkapan Surabaya Hull Construction Unit - Nanta Sigit; Sutanto Hidayat; Nelly Budiharti (International journal of technology and education research, 2025)
Construction is a high-risk activity that can lead to accidents. Workplace accidents can be caused by unsafe behavior. One way to reduce workplace accidents is by establishing a safety culture. A safety culture can be formed through the presence of factors that shape a safety culture. This study aims to examine the relationship between factors that shape a safety culture and safety behavior. This study is descriptive, observational, and uses a cross-sectional design. The population in this study was 73 respondents, and data were collected using a questionnaire. The independent variables were management commitment, occupational safety and health regulations and procedures, communication, competence, worker involvement in occupational safety and health, and the worker's social environment, while the dependent variable was safety behavior. the results showed that factors that shape a safety culture with a strong but weak relationship to safety behavior were management commitment, occupational safety and health regulations and procedures, and worker involvement. Factors that shape a safety culture that have a strong relationship to safety behavior were communication (c = 0.414) and the worker's social environment (c = 0.477). It is recommended that companies optimize safety culture through communication and the social environment of workers by holding safety talks and safety inductions.